Movement Coordination: Factor Structure of Development in 5th-7th Grade Girls - O. Ivashchenko; V. Prykhodko; M. Cieslicka (Physical Education Theory and Methodology, 2018)
The study objective is to determine the structure of coordination abilities development in 5th-7th grade girls.